Преемственность между начальным и средним звеньями школьного обучения - Миллер, Т.Б. (My University, 2016)
This article deals with problem of continuity between primary and secondary school education units, the features of each period, an adaptation of first-graders to the school environment, their cognitive pro- cesses of restructuring, changes in the behavior of pupils, in the relationship between teachers and pupils.
Keywords: an adaptation of first-graders to the school; continuity; an effective influence on the development of s pupils' thinking; keeping the psychological features of the pupils; pedagogical collaboration